Tensile Test of Chicken Feather Fibre Composite Material and Application - Firmansyah, Arfin; Irawan, Doddy; Fuadzen Fuadzen; Sarwono, Eko (International Journal of Industrial Innovation and Mechanical Engineering, 2025)
The purpose of this study is to perform the tensile tests on chicken feather fiber composites to evaluate their potential in practical engineering applications. The study employed the experimental method as a laboratory activity, in which chicken feathers fibers were fused with epoxy resin at different ratios of 5%, 10%, 12% and 14% to form composite specimens. In order to find the ultimate tensile strength, yield strength and the modulus of elasticity of the composites, tensile testing of the composites was done according to the the American Society of Testing and Materials (ASTM) D3039 standard test method. Results showed that in as low as 5% cement reinforcement of chicken feathers, the mechanical properties of the resin were greatly improved, with the ultimate tensile strength reaching 48.672 N/mm² and the yield strength being 39.168 N/mm². This shows the promise of using chicken feather fiber composites as strong and light materials that are also eco-friendly for various uses. The discussion topics mentioned the behavior of stress-strain transition from elastic to plastic region on increasing the load, which showed the strength and flexibility of the composites are in essence, the opposite of each other. This study advances the view that there is more development to be done on chicken feather fiber composites to enable them satisfy the standards of various sectors thereby offering an environmentally friendly method in cutting waste and reducing the burden of the environment from synthetic materials.